STUDENTS' PERCEPTIONS OF THE IMPLEMENTATION OF BLENDED LEARNING IN A LARGE ENGLISH CLASS - Fachri Ali; Eros Meilina Sofa (English Language Teaching Department (Prodi Pendidikan Bahasa Inggris), 2018)
This present study aims to explore Institut Agama Islam Negeri Pekalongan students’ perceptions regarding the implementation of combining the features of face-to-face instruction and online learning via Edmodo learning management system (LMS) called blended learning (BL) in their large English class. This research was conducted in the class consisted of 46 students who took English III course at the university. The participants completed three types of open-ended questionnaires. The findings reveal that the implementation of BL had a positive effect on perceived quality and student satisfaction in the teaching and learning processes. Most of the students commented that the implementation of BL helped make the course and activities interesting because of the technology integration in their large class. BL, likewise, encouraged them to enhance their language skills, particularly reading and writing. These results illustrate that the language skills could be also improved by incorporating the tremendous advancement of technology as a part of language instruction. Meanwhile, another finding reports that BL might have a better impact on the students’ level of engagement since most of the research participants rated themselves as more engaged in this blended course. Keywords: Blended Learning, Perceptions, Engagement, Large English Class